Association between Breast Milk and Bronchopulmonary Dysplasia: A Single Center Observational Study - Fonseca, Luciana T.; Senna, Denise C.; Silveira, Rita C.; Procianoy, Renato S. (American Journal of Perinatology, 2017)
Introduction Bronchopulmonary dysplasia (BPD) is a frequent, long-term complication in very low-birth-weight (VLBW) newborns. Its etiology is multifactorial and the oxidative stress is one of its main causes. Breast milk (BM) reduces oxidative stress and provides antioxidant protection, therefore, BM may have a protective effect against BPD.Objectives This study aims to assess the possible protective effects of BM on BPD.Methods This is a cohort study including infants with a birth weight below 1,500 g and/or gestational age of less than 32 weeks, born between January 2011 and October 2014. BPD was defined as the need for supplementary oxygen for 28 days or more.Results The incidence of BPD was 29.1%. The median amount of BM received by the patients in the first 6 weeks of life was significantly higher in patients without BPD (10.8 mL/kg/day) than in those with BPD (2.3 mL/kg/day). The amount of BM received was inversely associated with the incidence of BPD, even after multivariate analysis. The cutoff point at which the protective effect emerged was an average amount of 7 mL/kg/day of BM during the first 42 days of life.Conclusion Feeding VLBW infants with BM is associated with a lower risk of developing BPD.
Keywords: bronchopulmonary dysplasia; breast milk; very low-birth-weight infants; prematurity